2023
DOI: 10.3389/fpsyg.2023.1034561
|View full text |Cite
|
Sign up to set email alerts
|

Beat alignment ability is associated with formal musical training not current music playing

Abstract: The ability to perceive the beat in music is crucial for both music listeners and players with expert musicians being notably skilled at noticing fine deviations in the beat. However, it is unclear whether this beat perception ability is enhanced in trained musicians who continue to practice relative to musicians who no longer play. Thus, we investigated this by comparing active musicians’, inactive musicians’, and nonmusicians’ beat alignment ability scores on the Computerized Adaptive Beat Alignment Test (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…The final model included perceptual and motor measures derived from tasks which were shown to be affected by musical training in prior work. The detection of the alignment between a metronome and musical beat (Beat Alignement Test), and the perception of a rhythmic irregularity in an isochronous sequence (Anisochrony detection) are typically enhanced by musical training [66][67][68] . Similarly, performance in paced tapping to rhythmic stimuli (music and metronomes) is improved by musical training 28,29,69 (for a review, see 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…The final model included perceptual and motor measures derived from tasks which were shown to be affected by musical training in prior work. The detection of the alignment between a metronome and musical beat (Beat Alignement Test), and the perception of a rhythmic irregularity in an isochronous sequence (Anisochrony detection) are typically enhanced by musical training [66][67][68] . Similarly, performance in paced tapping to rhythmic stimuli (music and metronomes) is improved by musical training 28,29,69 (for a review, see 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…The heightened bilateral putamen activity observed in PG during the SynC could be tied to a robust internal sense of rhythm, as suggested by previous studies ( Grahn, 2009 ; Kasdan et al, 2022 ). Proficiency in aligning with beats, essential for defining musical tempo and rhythm, is associated with formal musical training ( Kindersley, 2012 ; Spiech et al, 2023 ). In multitasking scenarios, PG demonstrates the crucial ability to uphold a stable internal beat, particularly important for rhythmic drumming.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a difference observed in beat alignment and the time spent on musical practice [118]. Studies in musicians have shown that the more years a person is intensively engaged in music, the more areas of the brain are involved in perceiving, analyzing, and recording it, and the more neural networks develop to convey the language of music to wider areas of the brain and make it "musically driven".…”
Section: Discussionmentioning
confidence: 99%